2014
DOI: 10.1515/chem-2015-0037
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric pressure glow discharge in air used for ethanol conversion: experiment and modelling

Abstract: Abstract:Complex theoretical and experimental investigation of ethanol into syngas conversion assisted by DC atmospheric pressure discharge with plasma cathode is presented. Infrared absorption spectroscopy together with the equation for the conservation of the number of atoms at the inlet and outlet of the reactor are used to determine the composition of syngas, the main components of which are hydrogen, carbon monoxide, methane and acetylene. It is shown that the plasmachemical reactor enables efficient (ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Interestingly, the authors observed that the nature of the diluent gas played a significant role in the H 2 yield, where the H 2 yield was 2−3 times higher in the NH 3 /He mixed feed when compared to the NH 3 /Ar mixed feed for the same flow rate and power input. 287 Only at NH 3 concentrations <20% was the H 2 yield similar for both diluents. The Ar was observed to affect the discharge stability negatively compared to when He was used as the diluent.…”
Section: Advancements and Currentmentioning
confidence: 95%
See 3 more Smart Citations
“…Interestingly, the authors observed that the nature of the diluent gas played a significant role in the H 2 yield, where the H 2 yield was 2−3 times higher in the NH 3 /He mixed feed when compared to the NH 3 /Ar mixed feed for the same flow rate and power input. 287 Only at NH 3 concentrations <20% was the H 2 yield similar for both diluents. The Ar was observed to affect the discharge stability negatively compared to when He was used as the diluent.…”
Section: Advancements and Currentmentioning
confidence: 95%
“…286 It was not until the early 2000s when Arkhipenko et al provided another report of NH 3 decomposition in mixed He/ NH 3 and Ar/NH 3 feed streams using an atmospheric pressure glow discharge (APGD) plasma. 287 The authors observed NH 3 conversion of ∼60% at a flow rate of 0.5 L/min. Interestingly, the authors observed that the nature of the diluent gas played a significant role in the H 2 yield, where the H 2 yield was 2−3 times higher in the NH 3 /He mixed feed when compared to the NH 3 /Ar mixed feed for the same flow rate and power input.…”
Section: Advancements and Currentmentioning
confidence: 97%
See 2 more Smart Citations